¿Judge and jury? Advantages and disavantages of the transfer of materially administrative faculties to a materially jurisdictional body - Gonzalez Beltrones, Adria Velia (UNIVERSIDAD DE SONORA, 2018)
Introduction.It is proposed return to the body (s) of internal control(s) of the direct and parastatal public administration of Sonora, Secretariat of the General Comptroller's Office and of the external control (Superior Institute of Tax Auditing ISAF in Sonora, and their local counterparts and federal) the power to determine in the terms provided by the law, the penalties applicable to state, municipal and / or federal public servants, for serious administrative responsibility, to individuals who commit acts related to serious administrative offenses, to individuals in special situation, ……and other powers granted by law as appropriate.